Morphometric analysis of early regeneration of motor axons through motor and cutaneous nerve grafts - Ghalib, N; Houst'ava, L; Haninec, P; Dubový, P (Annals of anatomy, 2001)
Peripheral nerve damage is a frequent consequence of trauma, tumor surgery or diseases. Clinical results of functional reinnervation after the application of cutaneous grafts are still unsatisfactory. Differences in the extracellular matrix are considered to be one of the factors responsible for poor results of motor axon reinnervation through the cutaneous graft. To verify these differences, we compared morphological features of the motor axons regenerating through the graft prepared from the saphenous nerve and the motor branch of the femoral nerve. Eighteen female adult rats (Wistar) were used in experiments. The saphenous nerve, the femoral nerve, and its main motor branch were exposed under deep anesthesia with ketamine and xylazine. The nerve graft (10 mm) prepared from the saphenous nerve was applied between the stumps of the transected motor branch of the femoral nerve in the 6 rats. In the next 6 rats, the nerve graft (10 mm) harvested from the motor branch of the femoral nerve was inserted between stumps of the transected motor branch of the femoral nerve on the contralateral side. All rats were perfused with Zamboni's fixative solution 14 days after grafting. The samples of grafts and the intact motor branch (n = 6) were dissected and embedded in Durcupan ACM. Semithin sections stained with Toluidine Blue were used for morphometric analysis of myelinated axons by means of computer-assisted image analysis system. Ultrathin sections counterstained with uranyl acetate were viewed and photographed in an electron microscope. The number of myelinated motor axons showing early regeneration under conditions of the cutaneous and motor nerve grafts was similar. The diameter of axons and thickness of their myelin sheaths were significantly smaller when the axons regenerated into the saphenous nerve in contrast to the motor graft. Morphometric analysis of early regeneration of myelinated motor axons suggests that the cutaneous and motor branches of the femoral nerve provide different conditions not for the growth but for the maturation of motor axons.
Keywords: Animals; Motor Neurons; Skin Transplantation; Female; Rats, Wistar; axony; transplantace kůže; Microscopy, Electron; ženské pohlaví; autologní transplantace; Peripheral Nerves; Nerve Fibers, Myelinated; kůže; elektronová mikroskopie; regenerace nervu; Nerve Regeneration; počítačové zpracování obrazu; Skin; periferní nervy; motorické neurony; krysa rodu Rattus; odběr tkání a orgánů; Tissue and Organ Harvesting; zvířata; Transplantation, Autologous; nervová vlákna myelinizovaná; Rats; Image Processing, Computer-Assisted; potkani Wistar; Axons